Transformational Leadership Strategies for Fostering the Interests and Talents of Students With Special Needs in Special Education School - Sandrinabila, Mutiara; Ginanto, Dion; Istofa, Dian Nisa (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the strategies, constraints, and challenges of transformational leadership exercised by the school principal in developing the interests and talents of students with special needs (ABK) at the Special Education School (SLB) Sri Soedewi Jambi amid limited facilities and infrastructure. This research is qualitative with a case study design. A descriptive qualitative approach was employed to gain an in-depth understanding of the principal's leadership practices within the context of special education. Data were collected through interviews, observations, and document analysis involving the principal as the key informant, as well as vice principals responsible for facilities and infrastructure, student affairs, and curriculum. Data analysis was conducted through data reduction, matrix development, coding, theme construction, and alignment with relevant theories. The findings indicate that the principal implements transformational leadership through four main dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Leadership strategies reflected in these dimensions include idealized influence demonstrated through consistency, commitment, and exemplary behavior in building trust among school members. Inspirational motivation is realized by fostering optimism and collective spirit despite the school’s limited facilities following a fire incident. Intellectual stimulation is evident in the encouragement of teachers’ creativity and innovation in utilizing available resources. Meanwhile, individualized consideration is reflected in mentoring practices tailored to students’ abilities and interests. The study also reveals challenges such as limited facilities and infrastructure, budget constraints, and increasing demands on teachers’ creativity. Nevertheless, the principal’s transformational leadership has proven effective in sustaining programs for developing the interests and talents of students with special needs through adaptive strategies and the strengthening of shared motivation and commitment.